Weed control and production aspects of strawberry in different ground covers - Tonin, Jeferson; Machado, José Tobias Marks; Sobucki, Lisiane; Benati, Jorge Atilio; Rohrig, Bruna; Schneider, Evandro Pedro (Revista de Ciências Agroveterinárias, 2017)
The objective was to evaluate strawberry productivity under different soil cover, as well as its effectiveness on the weed control in an organic production system. The experiment was conducted in the Universidade Federal da Fronteira Sul - UFFS, campus Cerro Largo. The random blocks delineation with 6 blocks was used. The units were designed using 10 “aromas” cultivar plants, planted in 4 interspersed lines each 0,3m apart. The treatments used were whole plants of Sudan grass (Sorghum sudanense), shavings, acicula of Pinus (Pinus elliottii), black polyethylene and uncovered soil. To determine the productive aspects, the mass production, number and size of fruit were evaluated. The effectiveness of the weed control under different soil cover was determined through the dry weed mass collected monthly. With the exception of the sudan grass, all the other treatments statistically matched the productive aspects. The black polyethylene cover presented better weed control.